Upright patient positioning for gantry-free breast radiotherapy: feasibility tests using a robotic chair and specialised bras - Boisbouvier, Sophie; Underwood, Tracy; McNamara, Joanna; Probst, Heidi (Frontiers in Oncology, 2023)
For external beam radiotherapy using photons or particles, upright patient positioning on a rotating, robotic chair (a gantry-less system) could offer substantial cost savings. In this study, we considered the feasibility of upright breast radiotherapy using a robotic radiotherapy chair, for (i) a cohort of 9 patients who received conventional supine radiotherapy using photons for a diagnosis of primary breast cancer, plus (ii) 7 healthy volunteers, selected to have relatively large bra cup sizes. We studied: overall body positioning, arm positioning, beam access, breast reproducibility, and comfort. Amongst the healthy volunteer cohort, the impact of specialised radiotherapy bras upon inframammary skinfolds (ISF) was also determined, for upright treatment positions. In conclusion, upright body positioning for breast radiotherapy appears to be comfortable and feasible. Of the 9 patients who received conventional, supine radiotherapy (mean age 63.5 years, maximum age 90 years), 7 reported that they preferred upright positioning. Radiotherapy bras were effective in reducing/eliminating ISF for upright body positions, including for very large breasted volunteers. For upright proton radiotherapy to the breast, beam access should be straightforward, even for arms-down treatments, as en-face field directions are typically used. For photon radiotherapy, additional research is now required to investigate beam paths and whether, for certain patients, additional immobilization will be required to keep the contralateral breast free from exposure. Future research should also investigate arm supports custom-designed for upright radiotherapy.